Comparison of elbow joint isokinetic strength and reaction times of racquet players - Gurkan, Kaan; Golunuk Baspinar, Sebiha (Progress in Nutrition, 2020)
Study Objectives: This study aimed to compare racquet players’ elbow joint isokinetic supinationpronation strength and reaction times. Methods: study sample consisted of a total of 48 healthy male volunteers including 12 table tennis players (TP), 12 badminton players (BP), 12 court tennis players (CP), and 12 sedentary controls (SC). Isokinetic strength bilateral elbow supination-pronation strengths were measured at two different velocities (300/sand 1200/s) using an isokinetic dynamometer while bilateral hand movements were aurally and visually recorded using a NewTest 1000 instrument in 4 different ways to determine reaction times. Results: CP had higher isokinetic 300/s and 1200/s supination right elbow and 1200/s left supination elbow values than BP, TP, and SC (p<0.01). The isokinetic 300/s and 1200/s pronation right elbow isokinetic strength values of CP significantly differed from those of SC and TP. There were significant differences in mean visual and auditory reaction times between CP and SC (p<0.05). Conclusion: CP had higher isokinetic strength mean score than SC, BP and TP. The visual and auditory reaction times of CP were better than those of SC and similar to those of BP and TP.